Policy analysis of enlightenment dentist graduate internship program (A study of Permenkes No. 39 year 2017: Analisis kebijakan pemahiran lulusan dokter gigi melalui program internship: Kajian Permenkes No. 39 Tahun 2017 - Andriansyah .; Leny Sang Surya (Makassar Dental Journal PDGI Makassar, 2019)
Internsipisenlightenmentandautomationofdoctorordentistwhois part of the mandatory placement of temporary, a maximum of 1 (one) year. Based on Law No. 20 of 2013 on Medical Education states that doctors and dentists must take internshipas a continuation of the program profession,meansthatin the aforementioned articlepassthe competency test alone will not suffice as a condition to practice independently as dental recent graduates will be requiredtofollowinternshipforoneyearinahospital or health center designated,willing or not,it seems internship in dental education has become a sure thing after discharge Permenkes No 39 year 2017 on the Implementation of the program internship Doctors and Dentists Indonesia. Internship is one of dedication to the people and help the government to equalization dentist in Indonesia, so that dentists who have passed are not many living in large cities. Not only that, internship also assist dentists in seeking experience of dealing with clients directly with the patient's condition varies according epidemiology, provides the opportunity for dentists who have recently graduated to enlight competencies acquired during their education, so be a mature dentist in proceed further competence. Internsip dentist should be supported by the infrastructure of adequate dental practice in accordance with the standards, and ensure the health and safety, and welfare of dentists who are placed in the corners of Indonesia. Internship mechanism less obvious cause internship doctor is confused. The possibility of back-log or buildup internship participantsalso need to be considered.